On the term of standard language - Smetonienė, Irena; Smetona, Antanas; Valotka, Audrius (Lietuvių kalba, 2016)
After we started direct communication and collaboration with foreign scholars, we immediately noticed that one of the reasons of miscommunication derives from the lack of discussion of terminological synonymy as well as the concept of a term. For example, miscommunication may occur due to such issues as the understanding and the relationship of such terms as a borrowing and a foreign word, such Lithuanian words as naujadaras, naujažodis and neologizmas which are usually all rendered in English as a neologism, language policy and language planning, etc. In addition, numerous debatable issues arise regarding the use of the term marker and its synonyms in the context of morphology and the choice of different terms to refer to the administrative style (kanceliarinis, dalykinis, administracinis stilius in Lithuanian). There is a tendency to opt for an international term since it facilitates communication with foreign scholars. This article explores terms that deal with language ‘standardness’ used in linguistic research and in written public discourse. In addition, it raises a question of whether it would not be useful to replace the term of common language with that of standard language. In our opinion, the term standard language better reflects such aspects of a given language variety as its normative nature, national status, formality, a consistent and natural acquisition of the language system as well as the application of the acquired knowledge in the processes of language standardisation and language policy. Certainly, replacing a term with a different one is not difficult, i.e. it is a matter of agreement and intention; however, in our case the question seems to be directly related not only to terminology but also to the concepts that they signify. On the one hand, international practice shows that local terms remain local and cause problems in translating them into other languages; on the other hand, it also reflects differences in the content of the terms when they are used to refer to different stages of language development.Several terms were used in Lithuanian linguistics to refer to language standardness. Jonas Jablonskis used the term written language. The scholar emphasised that he chose the term deliberately since he was not aiming at codifying spoken language and since written language was deemed as the most important in his time. The term common language created by Pranas Skardžius entered public use only in 1927. However, after 1950, the term of common language was replaced by the Russian term literary language. It was no better than other terms, it had no traditions in Lithuania but it was important as a political stance of showing how united Soviet linguistics was. Such purposeless change of terms was not accepted well by linguists working both in Lithuania and abroad. This issue was discussed on many occasions in writings by Skardžius, Jonikas and it was debated widely by Lithuanian linguists. The term common language was started to be used again in 1969.Today the status of our language is different: we have the system of established vocabulary, grammar, the whole language system is standardised, we have institutions that set and monitor language norms (State Commission of the Lithuanian Language and the State Language Inspectorate), institutions that foster Lithuanian, standardised language is used in all public domains, its status is established by a special law. As a result, contemporary situation can be defined by two clear terms: 1) Lithuanian which encompasses dialects, sociolects, idiolects and which also subsumes borrowings and jargon since it is part of our daily language which is not regulated by any laws or resolutions; 2) standard language which is understood as a language variety of the highest prestige. We do not suggest that the use of the term common language should be abandoned but we believe it should have a different place in the system of terms. As we are familiar with the way language development processes are termed in other countries the examples of which are provided in the first part of this article, we argue that common language may refer to a certain stage in the development of our language. Thus the language of a pre-standard stage used by the whole nation which has been more or less standardised can be referred to by the term common language. It would involve such language use which occurs in the initial stages of the development of a standard language, i.e. it would no longer refer to some tribal or dialectal language but rather to the general language used by the whole nation or its substantial part which first occurs in a written form and which is standardised only on the primitive or intuitive level without any language policy at the national or any other institutional level. However, this stage is over now and therefore, similarly to Latvians, we have to use the term standard language. In our opinion, standard language is a standardised language variety which is used in public discourse (state management, media, school) and in international communication.
Keywords: Lithuanian; common language; standard language; literary language; general language